Bearings-Only target passive location - Mallaina, E. (2002)
This paper addresses a performance analysis of the principal algorithm for passive location target detection. This algorithm is based on maximum likelihood estimation. Finally a estimator accuracy comparison is done as a function of the number of sensors and measurements per sensor.